Maximum compressive stress analysis in upper central incisors rehabilitated with fiberglass posts and three types of crowns. A study with the finite element method. - Chávez Vela, Mayra J. (2022)
Objective: To evaluate the maximum compressive stress in maxillary central incisors restored with fiberglass posts and three types of crowns by the FEM finite element method. Materials and methods: The study was a virtual, descriptive, and laboratory trial. Three virtual models were made using the SolidWorks 2017 software from upper central incisors rehabilitated with fiberglass posts and a metal-ceramic crown, a monolithic lithium disilicate crown, and a zirconium-ceramic crown. They were then subjected to an oblique occlusal load of 150N with an angulation of 45°, distributed towards the palatal aspect. The stress analysis proceeded by comparing the maximum, minimum, and equivalent von Mises stresses. Results: The maximum compressive stress was found at the cervical level in the vestibular area of each of the crowns. Zirconium-ceramic crown (Design 3) was the one with the highest compressive stress with 73.89 MPa, followed by Lithium Disilicate crown (Design 2) with 63.42 MPa and the metal-ceramic crown (Design 1) with 48.4 MPa. Conclusion: The zirconium-ceramic crown better distributes the stress along the tooth since, due to its rigidity, it absorbs the stresses that are concentrated especially in the cervical area, which could indicate that it is the most appropriate option to rehabilitate endodontically treated teeth.